A Computer-Assisted Register and Information System for Diabetes - Jones, R. B.; Hedley, A. J.; Peacock, I.; Allison, S. P.; Tattersall, R. B. (Methods of Information in Medicine, 1983)
A new computer-assisted follow-up register and information system has been developed for patients with diabetes. The task of collecting and coding clinical information has been simplified, and methods of working in clinics have been adjusted to fit closely with the design of the new system.A flexible program suite includes statistical programs which allow clinical audit and evaluation of long term care to be carried out on demand. The system, which is on-line, operates under DSM 11 (DEC MUMPS) on a PDP 11/44 computer and, for hospital work, includes a video display unit and printer in the outpatient clinic and hospital ward.Registration of patients in the system may be carried out from either a hospital clinic or general practice. The clinical data base, completed at registration or review for each patient, is used to generate three computer-printed structured medical records .for use by hospitals, general practitioners and patients.The system can be used to provide (a) more reliable and effective record-keeping for patients and doctors, (b) automatic clinical audit for individuals or groups of patients, (c) data for long-term evaluation of care and other clinical research.
Keywords: Case Register; Computerized Medical Records; Patient-held Records; Diabetes; Long-term Follow-up